Modeling soil carbon stocks and carbon dioxide emissions (GHG) in production systems of Plain Altillanura (Orinoquia, 2018)
The different soil management affects soil C stocks. Multivariate analysis of the modeling of soil C stocks (SOC0-T), soil C losses rates (-ΔC) and / or soil C gains (ΔC), greenhouse emissions (GHG) and removals (-GHG) atmospheric of CO2 associated with some physicochemical properties of soils in productive systems of High plains and other of lower mountains of the Orinoco region formed three distinct groups. Cluster I grouped improved pastures of Granada (S1) and coffee agroforestry systems (AFS) associated with banana and legumes of Villavicencio (S9), where gains of C (ΔC) and removal of atmospheric CO2 (-GEI) were averages ranging from ≈ 0.11 to -2.37 t C ha-1 yr-1 and -1.60 to -8.70 t CO2eq ha-1 yr-1; monocultures in rotation also were part of this group; Cluster II grouped rice monoculture of Villavicencio (S10) and pineapple of Puerto Lopez (S14) who had the highest losses of C (-ΔC) and soil atmospheric CO2 emissions (GHG) of ≈ -2.08 to - 2.35 t C ha-1 yr-1 of ≈ 7.62 to 8.62 t CO2eq ha-1 yr-1; Cluster III grouped to agroforestry system AFS of rubber and leguminous cover crops (S13) and silvopastoral systems (SSPs) of Acacia mangium and improved pastures of Puerto Lopez (S12) with the highest gains of soil C (ΔC) and removals of atmospheric CO2 (-GEI) of ≈ 0.373 to 2.64 t C ha-1 yr-1 and -1.36 to -9.67 ≈ t CO2eq ha-1 yr-1. Agroforestry systems are a good alternative for soil C sequestration in Altillanura Plana of Colombia.
Keywords: Climate change; land use; residues inputs; sustainable agriculture; tillage type